COMBINATION OF PATHOLOGY OF THE BRAIN AND THE OPTIC NERVE - Alexandra Safonenko; Elena Ioyleva; Evgeniya Kabanova; Tatiana Seregina (MNJ (Malang Neurology Journal), 2022)
The relevance of assessing the lesion of the visual analyzer with optic disc drusen and the possibility of identifying concomitant pathologies, increases with the introduction of the latest diagnostic techniques.In the S. Fyodorov Eye Microsurgery Federal State Institution, Moscow, a patient, 50 years old, complaining of episodic blurred vision. The diagnosis revealed the drusen of the optic nerve head and concomitant congenital neurological pathology. The patient was consulted by a neurosurgeon with the aim of delivering a diagnosis and determining treatment tactics. The diagnosis was made: Arteriovenous malformation of the deep arteries of the sections of the left parietal lobe. After assessing the size of the arteriovenous malformation, its location in the functionally important area of the brain, it was decided to follow up the patient in dynamics.Â